Composição centesimal, atributos sensoriais e custos de produção de carne de cordeiros alimentados com silagens de capim buffel - Silva, Eriane Guedes da (2017)
The objective of this study was to evaluate the potential use of buffel grass silage in replacement of corn silage in diets for lambs by determining the quality of the meat and the cost of production. The completely randomized design (CRD) was used, with four treatments and eight replicates. The diets were formulated by replacing the corn silage with buffel grass silage at increasing levels: 1) 100% CS and 0% BGS; 2) 66.6% CS and 33.3% BGS; 3) 33.3% CS and 66.6% BGS; 4) 0% CS and 100% BGS. Thirty-two Santa Inês mestizo sheep, male, uncastrated, approximately six months old and with a mean initial weight of 20.09 ± 2.0 kg were used. The chemical physical characteristics were not influenced (P> 0.05) by the levels of substitution of corn silage by buffel grass silage, except for luminosity variable (L). The weight losses due to cooking presented a quadratic effect, however, for the shear force variable, an increasing linear behavior was observed as the buffel grass silage levels were increased. There was no effect (P <0.05) for the percentages of ash, protein and lipids evaluated in the meat, respectively. For moisture, a linear effect (P <0.05) was observed for corn silage substitution levels by buffel grass silage, ranging from 73.02 to 74.76%, respectively. It was observed when evaluating the sensory parameters that there was no difference (P> 0.05) for the attributes color, aroma, softness, succulence and overall evaluation. The different levels of substitution of corn silage for buffel grass silage influenced (P <0.05) the economic indicators, with the exception of the Net Operating Income. It concludes that the meat produced meets the requirements of the consumers, as well as the use of buffel grass silage in the diets, constituting a relevant alternative in relation to production costs, for lamb terminations in semi-arid regions.